2023
DOI: 10.2166/ws.2023.025
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera: a sustainable method to treat fluoride-contaminated water

Abstract: Excessive fluoride (F) is introduced into the water either by natural phenomenon or by industrial effluents. However, F in adequate amounts is necessary for sustaining good dental health. Contrarily, F concentrations in drinking water surpassing 1.5 mg/L may, nevertheless, be harmful to human health. F pollution in drinking water is a serious and challenging problem that affects people all over the world. Adsorption appears to be an effective, environmentally beneficial, and cost-effective approach to eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Thus, the initial concentration of uoride affects sorption. Analogous research (Chowdareddy et al, 2023) also demonstrated that as uoride initial concentrations increased, the adsorbents' e cacy in removing uoride decreased.…”
Section: Effect Of Initial Fluoride Concentrationmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, the initial concentration of uoride affects sorption. Analogous research (Chowdareddy et al, 2023) also demonstrated that as uoride initial concentrations increased, the adsorbents' e cacy in removing uoride decreased.…”
Section: Effect Of Initial Fluoride Concentrationmentioning
confidence: 85%
“…Similar ndings regarding the removal of uoride have been reported by numerous researchers. For example, Chowdareddy et al (2023) found that the pseudo-second-order reaction kinetic model best described the adsorption of uoride onto moringa-based adsorbent. Pseudosecond order kinetics has been successfully applied to a number of adsorption systems and suggests that the chemisorption step in the adsorption process determines the rate.…”
Section: Adsorption Kinetic Studiesmentioning
confidence: 99%